PHARMACEUTICAL SERVICES: STATUS AND DEVELOPMENT TRENDS - A. A. Klimenkova; L. N. Geller; A. A. Skripko; L. A. Gravchenko; E. A. Korzhavykh (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the review is to provide an analysis and generalization of the main directions of research in the sphere of pharmaceutical services, and their characteristics associated with the determination of their main development trends.Materials and methods. For the analysis, the information store on the basis of scientific publications by Russian and foreign scientists, devoted to research in the field of pharmaceutical services (PSs), has been used. The search for publications was carried out in the open and accessible sources of the latest twenty years (the retrospective period of 2001-2021), located in scientific and technical libraries of institutions, as well as in electronic databases: Elibrary, Medline / PubMed, Cochrane Library, Scopus, Cyberleninka, Google-academy, J-stage. When forming the information array, the search for publications was carried out according to the following requests: pharmaceutical services (pharmaceutical care services), the provision of pharmaceutical services, the quality of pharmaceutical services. For the conceptualization of the study, 87 scientific publications obtained as a result of information retrieval, have been used.Results. In the course of the study, a logical and structural analysis of the main directions in which research in the field of providing PSs in our country is developing, has been carried out. The main trends in the study of the providing services' activity in the sphere of drug circulation, are characterized. A comprehensive analysis of the category of "pharmaceutical service" has been carried out. The terminological content of this concept, the groups of features characterizing the economic and social essence of educational institutions have been generalized, and the most characteristic features that make up the structure and content of educational institutions, have been identified. The existing approaches to the development of the nomenclature and types of PSs have been analyzed and the systematization of pharmaceutical works and services using the process approach, have been proposed by the authors.Conclusion. The conducted study indicates the presence of several directions in the development of research in the field of providing PSs, aimed at improving the quality of services for the population in pharmaceutical organizations. However, the most important role in the research is assigned to the study and assessment of the quality of educational institutions, the development of approaches to its optimization. As evidenced by the results of the analysis and generalization, the most successful activity in the provision of services in the field of drug circulation requires the implementation of a process approach and the implementation of Quality Management Systems (QMSs).